Climate warming from managed grasslands cancels the cooling effect of carbon sinks in sparsely grazed and natural grasslands - Jinfeng Chang (Nature Portfolio, 2021)
Grasslands, and the livestock that live there, are dynamic sources and sinks of greenhouse gases, but what controls these fluxes remains poorly characterized. Here the authors show that on the global level, grasslands are climate neutral owing to the cancelling effects of managed vs. natural systems.